Does a Fine-Tuned Universe Tell Us Anything about God? - Hincks, Adam D. (Zygon, 2025)
The apparent fine-tuning of several fundamental parameters that determine the properties of our universe and make it hospitable to life is sometimes used as an argument for God from design. I review the concept of cosmic fine-tuning and critically examine the claim that God is its most probable cause. While not definitively repudiating this claim, I argue that it is potentially in tension with the more apophatic approach to God found in the Abrahamic traditions. I then offer a metaphysical analysis of the contingency of fine-tuning that situates it within the classical analogy of being that points to the Divinity.